Personal Capital and Female Labor Force Participation in Indonesia: A Probit Analysis of Urban–Rural Contrasts - Elita Pertiwi; Raden Muhamad Purnagunawan; Ferry Hadiyanto; Faisal Madjid Alyasa (Universitas Pendidikan Ganesha, 2025)
This study investigates the impact of personal capital, comprising education, ICT skills, and health, on female labor force participation (FLFP) in Indonesia, where FLFP remains low despite decades of economic growth. The research addresses a critical gap in understanding how individual human capital interacts with regional contexts to influence women’s participation in paid work. Using nationally representative data from the 2022 National Socioeconomic Survey, this study applies a probit regression model to estimate the probability of FLFP among working-age females, with separate analyses for urban and rural areas. Interaction terms are included to test whether ICT skills have greater effects at higher education levels. The results indicate that education exhibits a U-shaped relationship with FLFP. Marginal effect plots confirm this non-linear pattern, with participation lowest at mid-level education. When ICT is included, this negative effect is reduced, especially in urban areas, indicating that digital skills help enhance the value of education. Interaction plots show that ICT alone has little effect at low education levels but becomes increasingly beneficial as education levels rise, particularly in urban settings. Health, which encompasses physical, mental, and cognitive aspects, also has a significant positive impact on women’s participation. These findings suggest that policies should not only expand access to education and digital skills but also integrate health support to promote women’s employment. Enhancing digital infrastructure and tailoring interventions to local contexts may help reduce gender and regional gaps in FLFP.